BANGLADESH: BETWEEN COMPETING STRATEGIES AND GEOPOLITICAL RIVALRY IN THE INDO-PACIFIC - Mohammad Aynul Islam; Rubel Molla (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2025)
Indo-Pacific (IP) has been turned into an important theatre for strategic competition with the growing involvement of major powers. The US, India, Japan and China all are engaging in the region but through divergent approaches. They are coming up with competing strategies like IPS, FOIP, BRI to counter the common rivals. Geopolitical rivalry between the great powers frequently caused discomfort for the other nations in this region. Bangladesh as an emerging economic power is facing challenges and dilemmas due to the strategic competition. Bangladesh's position in the Indo-Pacific is defined by its strategic location and the competing interests of major powers. The country navigates this complex geopolitical landscape by balancing its relationships with these powers, engaging in strategic circumventing, and prioritizing its own national interests. The paper argues that Bangladesh has been pursuing four types of foreign policy goals: inclusive partnership, regional peace and stability, development priorities and defence cooperation.